Building a maker community around an open hardware platform - Morreale, Fabio; Moro, Giulio; Chamberlain, Alan; Benford, Steve; McPherson, Andrew P. (ACM Press, 2017)
This paper reflects on the dynamics and practices of building a maker community around a new hardware platform. We ex- amine the factors promoting the successful uptake of a maker platform from two perspectives: first, we investigate the tech- nical and user experience considerations that users identify as the most important. Second, we explore the specific activities that help attract a community and encourage sustained partici- pation. We present an inductive approach based on the case study of Bela, an embedded platform for creating interactive audio systems. The technical design and community building processes are detailed, culminating in a successful crowdfund- ing campaign. To further understand the community dynamics, the paper also presents an intensive three-day workshop with eight digital musical instrument designers. From observations and interviews, we reflect on the relationship between the platform and the community and offer suggestions for HCI researchers and practitioners interested in establishing their own maker communities.